A “Fundamentals” Train-the-Trainer Approach to Building Pediatric Critical Care Expertise in the Developing World - Crow, Sheri S.; Ballinger, Beth A.; Rivera, Mariela; Tsibadze, David; Gakhokidze, Nino; Zavrashvili, Nino; Ritter, Matthew J.; Arteaga, Grace M. (Frontiers in Pediatrics, 2018)
Pediatric Fundamental in Critical Care Support (PFCCS) is an educational tool for training non-intensivists, nurses, and critical care practitioners in diverse health care settings to deal with the acute deterioration of pediatric patients. Our objective was to evaluate the PFCCS course as a tool for developing a uniform, reproducible, and sustainable model for educating local healthcare workers in the optimal management of critically ill children in the Republic of Georgia. Over a period of 18 months and 4 visits to the country, we worked with Georgian pediatric critical care leadership to complete the following tasks: 1) Survey health care needs within the Republic of Georgia, 2) Present representative PFCCS lectures and simulation scenarios to evaluate interest and obtain “buy-in” from key stake-holders throughout the Georgian educational infrastructure, and 3) Identify PFCCS instructor candidates. Georgian PFCCS instructor training included the following steps 1) US PFCCS consultant and content experts presented PFCCS course to Georgian instructor candidates. 2) Simulation learning principles were taught and basic equipment was acquired. 3) Instructor candidates presented PFCCS to Georgian learners, mentored by PFCCS course consultants. Objective evaluation and debriefing with instructor candidates concluded each visit. Between training visits Georgian instructors translated PFCCS slides to the Georgian language. Six candidates were identified and completed PFCCS instructor training. These Georgian Instructors independently presented the PFCCS course to 15 Georgian medical students. Student test scores improved significantly from pre-test results (n=14) (pretest: 38.7±7 vs post-test 62.7±6, p<0.05). A Likert-type scale of 1 to 5 (1 = not useful or effective, 5= extremely useful or effective) was used to evaluate each student’s perception regarding 1) relevance of course content to clinical work students rated as median (IQR): a. Relevance of PFCCS content to clinical work, 5 (4-5); b. Effectiveness of lecture delivery, 4 (3-4); and c. Value of skill stations for clinical practice, 5 (4-5). Additionally the mean (±SD) responses were 4.6 (±0.5), 3.7 (±0.6) and 4.5 (±0.6) respectively. Training local PFCCS instructors within an international environment is an effective method for establishing a uniform, reproducible, and sustainable approach to educating healthcare providers in the fundamentals of pediatric critical care.